Reusable Fe3O4/SBA15 Nanocomposite as an Efficient Photo-Fenton Catalyst for the Removal of Sulfamethoxazole and Orange II - Jorge González-Rodríguez; Lucía Fernández; Zulema Vargas-Osorio; Carlos Vázquez-Vázquez; Yolanda Piñeiro; José Rivas; Gumersindo Feijoo; Maria Teresa Moreira (Nanomaterials, 2021)
Today, the presence of recalcitrant pollutants in wastewater, such as pharmaceuticals or other organic compounds, is one of the main obstacles to the widespread implementation of water reuse. In this context, the development of innovative processes for their removal becomes necessary to guarantee effluent quality. This work presents the potentiality of magnetic nanoparticles immobilized on SBA-15 mesoporous silica as Fenton and photo-Fenton catalysts under visible light irradiation. The influence of the characteristics of the compounds and nanoparticles on the removal yield was investigated. Once the key aspects of the reaction mechanism were analyzed, to evaluate the feasibility of this process, an azo dye (Orange II) and an antibiotic (sulfamethoxazole) were selected as main target compounds. The concentration of Orange II decreased below the detection limit after two hours of reaction, with mineralization values of 60%. In addition, repeated sequential experiments revealed the recoverability and stability of the nanoparticles in a small-scale reactor. The benchmarking of the obtained results showed a significant improvement of the process using visible light in terms of kinetic performance, comparing the results to the Fenton process conducted at dark. Reusability, yield and easy separation of the catalyst are its main advantages for the industrial application of this process.